Image Quality Inprovement for Small Vessel in Diabetic Foot Arteriography Using Dual-energy Computed Tomography - Yikai ZANG; Jing LI; Xiuliang LU; Cheng YAN (CT Lilun yu yingyong yanjiu)
Objective: To investigate the feasibility of dual-energy computed tomography (DECT) in foot arteriography for small vessel image quality in patients with diabetes . Methods: A total of 30 patients with diabetes were enrolled prospectively between January and November 2022 in the radiology department of our hospital, where DECT was acquired immediately after the CT angiography (routine CTA group) of the lower extremity.The optimal virtual monochromatic images (DECT group) were derived from the DECT data. Image quality was assessed by measuring the CT values and noise in foot arteries, and signal-tonoise ratio (SNR) and contrast-to-noise ratio (CNR) were calculated. The arterial course and small vessel display were scored using a 5-point scale (1, poor; 5, excellent). Results: The CNR and SNR were significantly better in the DECT group than in the routine CTA group. The DECT group received higher subjective scores on the posterior tibial artery and the foot arteries (all > 3) than did the routine CTA group. Conclusion: Compared to the routine CTA imaging, DECT offers superior image quality for foot arteriography, thereby enhancing the diagnostic accuracy of foot arteriography and bolstering physicians’ confidence in disease diagnosis.